Accounting for Assignments - Victor G. Getman (Учёт. Анализ. Аудит)
The whole range of issues connected with the assignment agreements are critically assessed in the article. Economic essence of this phenomenon is analyzed. Different methods of accounting for it are critically scrutinized in the article. The article investigates the approaches of different commercial courts to the case settlements regarding the lawfulness of creation of the reserves of bad debts and doubtful receivables in business transactions according to the assignment agreement by the commercial organizations. Most of the courts consider that there are no grounds for their formation. However, according to the author of the article, this approach is lawful only regarding the acquisition of the standard receivables. In cases with the purchase of unconventional receivables the price discounts obviously point at the fact that most likely they are bad debts. Taking into account the dual nature of the discounts, the new order of accounting for assignment agreements is provided.